Teacher perception of changes in teaching methods caused by the COVID19 pandemic: a case study of teacher experiences during remote learning in a rural school district - Hibbs, Jamie (Kansas State University, 2024)
The COVID-19 global pandemic created unprecedented change on how teachers were expected to adapt/pivot/change their instructional practices. The purpose of this study is to examine teacher experiences and their perceptions of change to their classroom instruction due to the pandemic. For many teachers, this was their first experience with online or remote learning. These changes may or may not influence teachers continued use of these tools in the future, post-pandemic. A qualitative case study is conducted to collect the actual experiences and perceptions of teachers during the 20-21 school year in one rural school district as they implemented changes and constructed new ways to teach during the pandemic. A survey and interviews were conducted to identify the correlation between years of experience and ability to adapt to teaching in a new mode. Implications include how change is accepted and implemented by teachers and how the pandemic could be a pivotal movement in the educational field.
Teachers’ experience of changes to their teaching methods because of the COVID19 pandemic: a case study of teacher experiences during remote learning in a rural school district
Keywords: Change theory; Middle school teachers; High school teachers; Teaching during covid; Pandemic; Teaching